Determinants of non-vaccination against pandemic 2009 H1N1 influenza in pregnant women: a prospective cohort study. - Romain Freund (Public Library of Science (PLoS), 2011)
Background In October 2009, the French government organized a national-wide, free of charge vaccination campaign against pandemic H1N1 influenza virus, especially targeting pregnant women, a high risk group for severe illness. The study objective was to evaluate pandemic flu vaccine uptake and factors associated with non-vaccination in a population of pregnant women. Methodology/principal findings In a prospective cohort conducted in 3 maternity hospitals in Paris, 882 pregnant women were randomly included between October 12, 2009 and February 3, 2010, with the aim to study characteristics of pandemic influenza during pregnancy. At inclusion, socio-demographic, medical, obstetrical factors and those associated with a higher risk of flu exposition and disease-spreading were systematically collected. Pandemic flu vaccine uptake was checked until delivery. 555 (62.9%) women did not get vaccinated. Determinants associated with non-vaccination in a multivariate logistic regression were: geographic origin (Sub-Saharan African origin, adjusted Odd Ratio aOR = 5.4[2.3-12.7], North African origin, aOR = 2.5[1.3-4.7] and Asian origin, aOR = 2.1[1.7-2.6] compared to French and European origin) and socio-professional categories (farmers, craftsmen and tradesmen, aOR = 2.3[2.0-2.6], intermediate professionals, aOR = 1.3[1.0-1.6], employees and manual workers, aOR = 2.5[1.4-4.4] compared to managers and intellectual professionals). The probability of not receiving pandemic flu vaccine was lower among women vaccinated against seasonal flu in the previous 5 years (aOR = 0.6[0.4-0.8]) and among those who stopped smoking before or early during pregnancy (aOR = 0.6[0.4-0.8]). Number of children less than 18 years old living at home, work in contact with children or in healthcare area, or professional contact with the public, were not associated with a higher vaccine uptake. Conclusions/significance In this cohort of pregnant women, vaccine coverage against pandemic 2009 A/H1N1 flu was low, particularly in immigrant women and those having a low socio-economic status. To improve its effectiveness, future vaccination campaign for pregnant women should be more specifically tailored for these populations.